An Exploratory Study On The Sustainability Issues In The Context Of Cultural Tourism Destination In An Ancient Water Town In China - Xiangxian, Yu; Binti Mohi, Zurinawati (Cuestiones de Fisioterapia, 2023)
Some People Call The Ancient Water Towns Of China "Living Museums" Because They Have Many Cultural Relics. The Fact That They Have Kept Their Old Buildings, Bridges, And Canals In Good Shape Is A Strong Illustration Of How They Have Been Devoted To Keeping Their Way Of Life Alive Since Ancient Times. Over The Years, They Have Been Able To Keep Vital Parts Of Their Culture Alive. These Include Both Traditional Festivals And Unique Ways To Express Oneself, Both Of Which Have Been Passed Down From One Generation To The Next. The Goal Of This Study Is To Look At The Sustainability Problems That Chinese Water Towns Have Had To Deal With Throughout The Years In Order To Keep The Cultural Tourism Alive In These Places. Some Examples Of Things That Belong Within This Category Include Canals, Buildings That Have Been There For A Long Time, And Habits That Have Been Around For A Long Time. Also, Even While Their Rising Popularity As Tourist Spots Has Led To Huge Economic Gains And More Exposure To History, It Has Also Caused Problems That Threaten Their Long-Term Survival. Tourism Can Help Conservation Efforts, Boost Local Economies, And Encourage Behaviours That Help Protect Intangible Cultural Heritage, But It Can Also Turn Heritage Into A Business, Displace Local People, And Harm Ecosystems That Are Already Fragile. As The Current Arrangement Shows, Managing Cultural Tourism Is Vital For The Survival Of Historic Water Towns. The Researchers Who Conducted The Study Believe That Management Choices, Enforced Regulations, And The Level Of Community Participation May Significantly Influence Cultural Tourism, Either Positively Or Negatively. In Order To Make Sure That These Communities Will Still Be There In The Future, It Is Vitally Important To Make Rules That Are Based On Being Responsible For The Environment. These Guidelines Should Include Things Like Controlling The Number Of Tourists, Protecting Water Resources, And Creating Real Cultural Experiences While Attending To Existing Sustainability Challenges.